Changes in Cardiometabolic Risk Among Obese Older Adults After a 12-Month Exercise and Diet Intervention. (29th May 2020) - Bragg, Anna; Crowe-White, Kristi; Ellis, Amy; Locher, Julie; Ard, Jamy; Studer, Matthew; Phillips, Frank; Samsel, Steven; Parton, Jason
Abstract: Objectives: Obesity imposes risk to cardiometabolic health; however, intentional weight loss in obese older adults remains controversial. Using data from the CROSSROADS Study (clinicaltrials.gov #NCT00955903), this ancillary study investigated effects of exercise with and without intentional weight loss on changes in cardiometabolic risk assessed by four risk-scoring tools. Methods: Participants (n = 134, 39% male, 23% African American, 70.2 ± 4.7 y) were randomized to exercise (n = 48), exercise + nutrient-dense weight maintenance diet (n = 44), or exercise + nutrient-dense caloric restriction of 500 kcals/day (n = 42). The following risk scores were calculated using baseline and 12-month data: Framingham risk assessment, Cardiometabolic Disease Staging (CMDS), metabolic syndrome classification by the International Diabetes Federation (IDF), and metabolic syndrome classification by the National Cholesterol Education Program's Adult Treatment Panel (ATP III). Generalized Estimating Equations were employed to determine differences between groups with ethnicity, sex, and age as covariates. Results: Group-time interaction was not significant in application of IDF or ATPIII. Group-time interaction was significant for Framingham and CMDS ( P  = 0.005 and 0.041, respectively). Upon post-hoc analysis, significant within-group improvements in Framingham scores were observed for exercise + weight maintenance ( P  < 0.001, r = −1.682) and exercise + weight loss ( P  = 0.020, r = −0.881). In analysis of between-group differences in Framingham scores, a significant decrease was observed in the exercise + weight maintenance group ( P  = 0.001, r = −1.723) compared to the exercise group. For CMDS, the exercise + weight loss group had significant within-group improvements ( P  = 0.023, r = - 0.102). For between-group differences in CMDS, the exercise + weight loss group showed significant risk score reduction ( P  = 0.012, r = −0.142) compared to the exercise group. Conclusions: Risk assessment by Framingham and CMDS showed greater sensitivity to change in cardiometabolic risk factors. Results suggest obese older adults can lower cardiometabolic risk by engaging in exercise + weight maintenance or exercise + weight loss by moderate caloric restriction. Funding Sources: R01AG033094 NIA, K07AG043588 NIA, P30DK056336 NIDDK.